Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.ejcts.2010.01.041
|View full text |Cite
|
Sign up to set email alerts
|

An aortic ring to standardise aortic valve repair: preliminary results of a prospective multicentric cohort of 144 patients☆

Abstract: Implantation of an external aortic ring provides a reproducible technique for aortic valve repair with satisfactory preliminary results. The ongoing CAVIAAR trial (Conservative Aortic Valve surgery for aortic Insufficiency and Aneurysm of the Aortic Root) will compare this standardised repair technique using an expansible aortic ring to mechanical valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…32 A new sinus prosthesis that can probably maintain physiological root anatomy is available 33 ; widespread use can be expected once conclusive midterm and long-term results on functional valve outcome are available. In addition, an aortic annuloplasty ring for annular downsizing and stabilization 34,35 may prove helpful in numerous reconstructive approaches to treat the leaking aortic valve, and its use also may increase in the future. In vitro evaluation of this device has delivered promising initial results.…”
Section: Discussionmentioning
confidence: 99%
“…32 A new sinus prosthesis that can probably maintain physiological root anatomy is available 33 ; widespread use can be expected once conclusive midterm and long-term results on functional valve outcome are available. In addition, an aortic annuloplasty ring for annular downsizing and stabilization 34,35 may prove helpful in numerous reconstructive approaches to treat the leaking aortic valve, and its use also may increase in the future. In vitro evaluation of this device has delivered promising initial results.…”
Section: Discussionmentioning
confidence: 99%
“…In our series [16] of 289 patients (228 reimplantation and 61 remodeling) operated from 1988 through 2007, the operative mortality was 1.7%. The operative mortality was 2.8% among 144 patients enrolled in a multicenter trial on the remodeling procedure and aortic annuloplasty reported by Lansac et al [42]. In a multicenter trial on the reimplantation technique using the Valsalva Graft reported by De Paulis et al [33] the operative mortality was 1.8% among 278 patients.…”
Section: Operative Outcomesmentioning
confidence: 99%
“…This might be partly explained by higher rate of cusp repair in bicuspid patients (72% of patients versus 28% of patients for tricuspid valves). Apart from high rate of cusp repair, better results in Group 3 also could reflect a learning curve or other confounding factors, since these patients were operated later (Lansac et al, 2010a(Lansac et al, , 2010b.…”
Section: 3mentioning
confidence: 99%
“…Expansible subvalvular annuloplasty is systematically added using an external expansible aortic ring in order to increase cusp coaptation height, while maintaining systolic expansibility. Ring is "open" in case of isolated aortic insufficiency or supra-coronary aneurysm, in order that it may be positioned below the coronary arteries without detaching them from the aortic root (Lansac et al, 2005a(Lansac et al, , 2006(Lansac et al, , 2009(Lansac et al, , 2010a(Lansac et al, , 2010b(Lansac et al, , 2010c(Lansac et al, , 2011a(Lansac et al, , 2011b.…”
Section: From Original Valve Sparing Procedures To a Physiological Apmentioning
confidence: 99%
See 1 more Smart Citation